Application of Good Governance Principles in Public Services: A Case Study of the Investment and Integrated One-Stop Service Office in Indonesia - Syamsiah Hasyim; Septi Hikmatun; Yudarti Yudarti; Muh. Faisal (Tinta Emas Institute, 2025)
This research aims to determine the application of good governance principles in the public services of the capital investment and one-stop integrated services (DPMPTSP) of Sinjai district. The method used in this research is a qualitative research method. The data collection techniques used in this research were observation, interviews and documentation. Meanwhile, the data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The data used in the research are primary and secondary data. The results of this research show that the application of Good Governance principles has been implemented optimally, because it has been adapted to public service standards including Accountability, Transparency, Rule of Law, Participation and Professionalism. Accountability is created through effective coordination, socialization and communication carried out by officers. Transparency is created by openness of information conveyed to the public both on social media and directly at the DPMPTSP office of Sinjai district. creation of legal rules with the existence of service operational standards which are the basic reference in serving the community. The creation of professionalism by assessing the performance of exemplary employees every 6 months means that DPMPTSP employees are pressured to always be professional in carrying out their duties and obligations in serving the community. The output of this research is as a scientific work or reference for future researchers related to the application of Good Governance principles in the Sinjai Regency Investment and One-Stop Integrated Services Service (DPMPTSP).